Nursing in fast-track total hip and knee arthroplasty: A retrospective study. Issue 3 (August 2015) - Specht, Kirsten; Kjaersgaard-Andersen, Per; Kehlet, Henrik; Pedersen, Birthe D.
Abstract Aim To describe the increased activity in total hip arthroplasty (THA) and total knee arthroplasty (TKA) from 2002 to 2012 in a single orthopaedic department, the organisation of fast-track and its consequences for nursing care. Methods Retrospective, descriptive design. Data collection; from the hospital administrative database, local descriptions of fast-track, personal contact and discussion with staff. Results The number of operations increased threefold from 351 operations in 2002 to 1024 operations in 2012. In 2012, THA/TKA patients had a postoperative mean LOS of 2.6/2.8 days. Nurses had gained tasks from surgeons and physiotherapists and thus gained more responsibility, for example, for pain management and mobilisation. Staffing levels in the ward in 2002 and 2012 were almost unchanged; 16.0 and 15.8 respectively. Nurses were undertaking more complicated tasks. Conclusion Nursing care must still focus on the individual patient. Nurses need to have enough education to manage the complex tasks and increased responsibility. To prevent undesirable outcomes in the future, there is a need to pay attention to the nursing quality in balance with the nursing budget. It may, therefore, be considered a worthwhile investment to employ expert/highly qualified professional nurses in fast-track THA and TKA units.